Flow equations in commercial gas piping system - Ahmad Fahmy, Jusoh (2010)
There are various types of flow equations in commercial gas piping system and this thesis will covered about the comparison of Cox and Pole‟s method. FORTRAN 90 software was used to validate the manual calculation of both equations and a comparative study was made. The analytical solutions of the resulting differential equations are obtained in the form of Cox and Pole‟s equations. The equations give functional relationship between flow rate, inlet pressure and outlet pressure, as well as pressure drop at any given length. The effect of pressure drop per segment on gas flow rate is presented. Both of the equation was calculated manually from the commercial area gas piping route and the syntax generated from the equations were compiled and executed in F90 with no errors. The Cox‟s method was found more economically with smaller pipe size but allowable pressure drop in each section, compared to Pole‟s method. The equations considerably enhance gas pipeline design in terms of both ease of usage and accuracy. A simple computer program in FORTRAN 90 is developed to handle these calculations.